Are CEOs and CFOs Rewarded for Disclosure Quality? - Hui, Kai Wai; Matsunaga, Steven R. (The Accounting Review, 2015)
ABSTRACT This study provides evidence regarding the importance that boards of directors place on effective communication with the investor community by examining whether CEO and CFO compensation are related to the quality of the firm's financial disclosures. Using an index derived from analyst forecast characteristics and management forecast accuracy to measure disclosure quality, we find changes in the annual bonus for both the CEO and CFO to be positively associated with changes in disclosure quality. We also find that the relation is stronger for high-growth firms, firms that have stronger governance structures, and for executives with lower equity incentives. Overall, our findings provide insight into the importance that boards place on effective communication with investors as a responsibility of the CEO and CFO and, therefore, provide them with contractual incentives to address the moral hazard problem associated with voluntary disclosures. JEL Classifications: M41.